2019
DOI: 10.3390/app9102172
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Absolute Value of Cerebral Blood Volume and Optical Properties in Term Neonates Immediately after Birth Using Near-Infrared Time-Resolved Spectroscopy: A Preliminary Observation Study

Abstract: The aim of this study was to use near-infrared time-resolved spectroscopy (TRS) to determine the absolute values of cerebral blood volume (CBV) and cerebral hemoglobin oxygen saturation (ScO2) during the immediate transition period in term neonates and the changes in optical properties such as the differential pathlength factor (DPF) and reduced scattering coefficient (μs’). CBV and ScO2 were measured using TRS during the first 15 min after birth by vaginal delivery in term neonates who did not need resuscitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The present study used NIRS technology for the evaluation of ΔCBV during the immediate neonatal transition in full-term neonates after vaginal delivery. Up to date there have been published reports on CBV during immediate neonatal transition in healthy full-term neonates ( 34 , 35 ), in preterm and full-term neonates with and without respiratory support ( 36 ) and in preterm neonates receiving sustained lung inflations ( 37 ). All these studies showed a decrease of CBV during the first 15 min.…”
Section: Discussionmentioning
confidence: 99%
“…The present study used NIRS technology for the evaluation of ΔCBV during the immediate neonatal transition in full-term neonates after vaginal delivery. Up to date there have been published reports on CBV during immediate neonatal transition in healthy full-term neonates ( 34 , 35 ), in preterm and full-term neonates with and without respiratory support ( 36 ) and in preterm neonates receiving sustained lung inflations ( 37 ). All these studies showed a decrease of CBV during the first 15 min.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of cerebral oxygenation and hemodynamics in the 30 min after birth, in the earlier period, is critical for evaluating the balance of oxygen delivery and demand in the brain. Morimoto et al and Schwaberger et al reported a decreased CBV in the first 15 min after birth in healthy vaginally delivered neonates 8 and in those delivered by cesarean section 28 . Furthermore, Morimoto et al reported a greater CBV decrement in vaginal deliveries than in cesarean sections during the first 15 min after birth in healthy neonates 9 .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, three-wavelength near-infrared time-resolved spectroscopy (TRS) is an advanced NIRS mode for measuring not only ScO 2 , but also the absolute value of cerebral blood volume (CBV), calculated from total Hb. CBV measurements using TRS have been used to monitor changes in cerebral hemodynamics after birth 8 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Kinoshita et al, who measured skeletal muscle oxygenation in the lower extremities during 3 h of continuous sitting, report that compression stockings suppress increases in extracellular water in the lower extremities, leading to reduced blood volume and oxygenation levels in skeletal muscles [17]. The study by Morimoto et al measured cerebral blood volume and optical properties in five term neonates from 2-3 min to 15 min after birth, and demonstrate that TD DOS can stably measure the cerebral hemodynamics of neonates in the labor room [18]. Sakatani et al examined the effects of aging, cognitive dysfunction, and brain atrophy on Hb concentrations and optical pathlengths at rest in the prefrontal cortex in 202 elderly subjects, concluding that TD DOS enables an evaluation of the relation between prefrontal oxygenation at rest and cognitive function [19].…”
Section: Cutting Edge Time Domain Diffuse Optical Spectroscopy and Immentioning
confidence: 99%